Student involvement in University activities shaping their leadership: case Study in Inapan Siswa Grantt, Universiti Utara Malaysia - Putri Nur Saidatul Shafinaz Rodzi (Penerbit Universiti Kebangsaan Malaysia, 2024)
In the dynamic landscape of higher education, the role of leadership in engaging and empowering students has emerged as a crucial factor for fostering academic excellence and holistic development. Students' involvement in university activities provides a platform for leadership development. This paper aims to show how student involvement and transformative outcomes significantly influence leadership among the students in the student residential hall, Inapan Siswa Grantt, Universiti Utara Malaysia (UUM). By employing a quantitative method, this study focuses on 30 undergraduate students at the student residential hall, INASIS Grantt, UUM, who have experience in leadership skills. The study's findings show that these five impacts of student involvement and five impacts of transformative outcomes could affect student engagement and growth in leadership.